Environmental fiscal policy in an endogenous growth model with human capital - Walid Oueslati (Fondazione Eni Enrico Mattei (FEEM), 2001)
This paper analyses environmental fiscal policy within a two-sector endogenous growth model with elastic labour supply. Pollution is modelled as a side product of production. The framework allows us to analyse the consequences of an environmental tax on the economic dynamics. Both transitional dynamics and balanced growth path are computed and the response to an environmental tax change is explored. Short-run and long-run welfare costs are computed too. We show that an environmental tax change induces a sharp contrast between short-run and long-run effects. The magnitude of this contrast depends on the agents' aptitude to substitute studying time for leisure.
Keywords: E62; I21; H22; Q28; O41; D62; 330; Endogenous growth; human capital; environmental externality; environmental tax; transitional dynamics; welfare cost; Ökosteuer; Neue Wachstumstheorie; Wohlfahrtsanalyse; Theorie